DERMATITIS CAUSED BY CENTIPEDE ENVENOMATION: A CASE REPORT - Pereira de Oliveira Pardal, Pedro; Aroldo Alves Arraes, Jose; Whitney Weekes, Keya; Apolônia da Costa Gadelha, Maria (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Accidents caused by centipedes in Brazil result in mild envenomation, where pain, erythema and edema are predominant. Cases rarely evolve to complication stages. This report presents a clinical case of dermatitis produced by an unidentified centipede, registered at the Toxicological Information Center of Belém-Pará, which evolved to blisters and necrosis. The patient underwent treatment with antibiotics and oral anti-inflammatory drugs, topical bactericides and surgical cleaning; resulting in cicatrization of the wound. The purpose of this report is to inform health professionals of the possibility of complications, which should be considered and dealt with conventionally.